Monitoring subsidence over submarine coal mines in the Sydney coalfield, Canada, by bathymetric methods - D. J. Forrester; R. C. Courtney (The Institute of Materials, Minerals and Mining, 1905)
Modern advances have led to sweep and multibeam bathymetric surveying techniques that yield three-dimensional images of the sea floor and have also produced high-powered personal computers with which to control the data and analyse the results. At Sydney, in Nova Scotia, the topography of the sea floor over the longwall workings was observed before and after mining with a precision echo-sounder in 1987-89, with sweep bathymetry in 1993 and with multibeam bathymetry in 1994-95. The results of the latter programme produced what was probably the first observation of a complete three-dimensional subsidence trough over a longwall panel 2 500 m x 168 m. The subsidence has been quantified to a sufficient degree of accuracy to allow simple trend analysis, which has shown that the pattern and shape of movements are similar to those found elsewhere but with significantly smaller maximum subsidence. A prediction model has been calibrated